ON THE POSSIBILITY OF USING THE METHOD OF IMPULSIVE ELECTROMAGNETIC FIELD OF EARTH OF ENGINEERING AND GEOLOGICAL PIONEERING - Чомко, Д.; Крамаренко, О.; Маджалі, Мох'д А.Тх. (Київський національний університет імені Тараса Шевченка, 2008)
It is rotined on the real examples, that by the effective enough method of research tensely deformed there is a method of the impulsive electromagnetic field of earth the state of constructions.

На реальних прикладах показано, що достатньо ефективним методом дослідження напружено-деформованого стану (НДС) конструкцій є метод імпульсного електромагнітного поля Землі (ІЕМПЗ).
ЕФЕКТИВНІСТЬ МЕТОДУ ПРИРОДНОГО ІМПУЛЬСНОГО ЕЛЕКТРОМАГНІТНОГО ПОЛЯ ЗЕМЛІ В ОБЛАСТІ ІНЖЕНЕРНО-ГЕОЛОГІЧНИХ ДОСЛІДЖЕНЬ